Ethno-Botanical Survey of Medicinal Plants Used in the Treatment of Snakebites in Engali Sub-County Kazo District. - Bogere, Mohammed (Kabale University, 2025)
Snakebite remains one of the most neglected health issues in many countries, including Uganda. With over 80% of Ugandans engaged in agriculture and residing in rural areas, they are highly susceptible to snakebite envenomation, particularly while farming or grazing livestock. The management of snakebites in Uganda has long been inadequate, leading many citizens to rely on medicinal plants as a primary treatment option. This study aimed to conduct an ethnobotanical survey of medicinal plants used to treat snakebites in Engari Sub-County, Kazo District. Data was collected through interviews and questionnaires from 24 informants, comprising 67% males and 33% females. The survey identified 17 plants used for snakebite treatment, with jack bean being the most commonly cited (54.2%). Herbs were the predominant life form of these medicinal plants (53%), and seeds were the most frequently used plant parts (32.6%).The findings indicated jack bean and star grass as the most frequently mentioned plants, with leaves and seeds being the most commonly utilized plant parts for snakebite treatment. The usage of specific plant parts and growth forms was significant. The study concludes that further research is needed to explore other medicinal plants used for snakebite management and to conduct experimental studies to assess the efficacy and determine the appropriate dosages of these plants.